Stop listening to the customer : try hearing your brand instead - Ferrier, Adam; Flemming, Jen (John Wiley & Sons Australia, Ltd, 2020)
The customer is not always right. Far from it. What the customer wants is often at odds with what is best for the business or brand. Adam draws on his years of creative agency experience, the wisdom of other voices, as well as marketing science to outline the dangers of listening to the customer too much and reveals what you can do about it. This book will show you how to build a strong brand or business.